B-fields and Dust in Interstellar Filaments Using Dust Polarization (BALLAD-POL). IV. Grain Alignment Mechanisms in the Cocoon Nebula (IC 5146) Using Polarization Observations from JCMT/POL-2 - Saikhom Pravash; Thiem Hoang; Archana Soam; Eun Jung Chung; Diep Ngoc Pham; Nguyen Bich Ngoc; Le Ngoc Tram (The Astrophysical Journal)
The polarization of starlight and thermal dust emission from aligned nonspherical grains provides a powerful tool for tracing magnetic field morphologies and strengths in the diffuse interstellar medium to star-forming regions, and constraining the properties of dust grains and their alignment mechanisms. However, the physics of grain alignment is not yet fully understood. The alignment based on radiative torques (RATs), known as RAT alignment or the RAT-A mechanism, is the most acceptable mechanism. In this work, we investigate the grain alignment mechanisms in the F13 (F13N and F13C) and F13S filamentary regions of the Cocoon Nebula (IC 5146) using observations of polarized thermal dust emission from James Clerk Maxwell Telescope/POL-2 at 850 μ m. We find that the polarization fraction decreases with increasing total intensity and gas column density in each region, termed a polarization hole. We investigate any role of magnetic field tangling in the observed polarization hole by estimating the polarization angle dispersion function. Our study finds that the polarization hole is not significantly influenced by magnetic field tangling, but is mainly due to the decrease in RAT alignment efficiency of grains in denser regions. To test whether the RAT-A mechanism can reproduce the observed results, we estimate the minimum alignment size of grains using RAT theory. Our study finds strong evidence for the RAT-A mechanism that can explain the polarization hole. We also find potential hints that the observed higher polarization fractions in some regions of the F13 filament can be due to the combined effects of both suprathermal rotation by RATs and enhanced magnetic relaxation, supporting the magnetically enhanced RAT mechanism.